2017
DOI: 10.5005/jp-journals-10064-0012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety ofNavayasa Churnain the Management of Iron Deficiency Anemia

Abstract: Introduction: Iron deficiency anemia (IDA) is a condition where deficiency of iron in the body leads to reduction in the number of red blood cells (RBC). Even though IDA is an easily manageable condition with excellent outcome, it is observed that modern iron preparation often irritates gastric mucosa and causes adverse effects. In Ayurveda, IDA can be correlated with pandu based on symptomatic similarity. Navayasa Churna is an iron containing herbomineral preparation used for the management of Pandu. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…These phytoactives also chelate Fe1 153,154 and might help to reduce gut dysbiosis that can result from the unabsorbed Fe. Several clinical studies conducted on Fe preparations used in Ayurveda to treat Pandu (IDA) have shown encouraging results without exhibiting the common side effects as seen with conventional modern Fe preparations [143][144][145][146][147][148][154][155][156][157][158][159][160][161][162][163] .…”
Section: Fig 5: Typical Process Of Bhasma Preparationmentioning
confidence: 99%
“…These phytoactives also chelate Fe1 153,154 and might help to reduce gut dysbiosis that can result from the unabsorbed Fe. Several clinical studies conducted on Fe preparations used in Ayurveda to treat Pandu (IDA) have shown encouraging results without exhibiting the common side effects as seen with conventional modern Fe preparations [143][144][145][146][147][148][154][155][156][157][158][159][160][161][162][163] .…”
Section: Fig 5: Typical Process Of Bhasma Preparationmentioning
confidence: 99%
“…[ 17 18 ] The evidence on the safety and efficacy of many Ayurvedic interventions is available in the public domain. [ 19 20 21 22 ]…”
Section: Introductionmentioning
confidence: 99%
“…While going through these drugs, properties such as Rasa, Guna, Virya, Vipaka and specific actions like Dipana, Pacana, Rasayana, Grahi as similar with Panduhara drugs which are mentioned in Bhavaprakasha Nighantu.Further clinical efficacy of these formulations has been scientifically proven. (Sarita S.N et al 2018)[60] and (Babita Yadav et al 2017) [61]. CONCLUSION There are 38 single drugs i.e., herbal, mineral and liquids has been mentioned in Bhavaprakasha Nighantu which have Panduhara action and additionally 19 drugs are mentioned in the formulations Punarnava Mandura and Navayasa Churna in Bhavaprakasha Samhitha.…”
mentioning
confidence: 99%